Ibadah di Masa Wabah (Studi Kasus 3 Masjid di Dusun Mlangi Yogyakarta) - Rizki Firmansyah (Departement of Comparative Study of Religions, 2020)
The World Health Organization announced that COVID-19 has become the official name of this disease, the Director of the World Health Organization stated that it is a virus that has spread around the world and needs to be watched out. As a result of this virus, all aspects of human life have fallen apart, starting from the economy, education, and worship. With high concern, all public activities in Indonesia were immediately stopped to cut the spread of COVID-19. Everyone must follow health protocols and carry out all activities at home, whether studying, working, or worshiping. However, some people ignore the caution from the government and religious leaders so they still carry out their activities as usual. Such is the case in the Pesantren hamlet, Mlangi, Yogyakarta. Interviews were conducted with takmirs at 3 mosques in Mlangi village, Jogjakarta and to several community leaders. The results showed that the 3 mosques agreed to make faith and closeness to the god are their motivation to continue carrying out religious activities at the mosque during the pandemic.